Comparison Of Performance And Perception Of Undergraduate Medical Students Towards Different Small Group Teaching Strategies - Habib, Maryam; Mudassir, Ghazala; Bhatti, Mahwish Majid; Ahmad, Rifat Nadeem (Journal of Rawalpindi Medical College, 2024)
Objective: The objective of this study is to evaluate the perception of students towards the effectiveness of small group teaching methods in pathology and to determine their performance in them. Methods: The perception of 512 medical students on the effectiveness of small group teaching methods which included Problem-Based Learning (PBL), Seminar (Conference style), Case-Based Discussion (CBD) and Team-based learning (TBL) was measured by using a prevalidated questionnaire. Their performance was compared with their perception by using assessment scores achieved in themes covered by small-group teaching strategies. Results: Participants chose PBL as a medium which increased their understanding of Pathology. They achieved the highest scores in topics covered by PBL with a significant p-value (p<0.001) by using ANOVA. Conclusion: It was concluded that PBL was the most preferred learning method.